Characterisation of needle edge quality using diffraction pattern. (July 2022) - Rani, Monika; Mishra, Vinod; Singh, Omendra; Shankar, Ajay; Kumar, Raj
Highlights: Diffraction based needle edge characterization technique is presented. The diffraction fringes around the needle edges are recorded to analyse the defects i.e. tip bending, chipping, and edge roughness. The proposed technique is simple, non-contact in nature, and capable to provide qualitative as well as quantitative evaluation. The presented technique has the potential for in-situ measurements of needles and other surgical tools in biomedical engineering. Abstract: The performance of hypodermic needles is mainly dependent on quality of their edges. The quality of the needle edges directly impacts penetration forces, tissue healing time, and patient pain. At present, only subjective techniques are used to access quality of edges of the needles which are not capable to contribute during manufacturing. Thus an appropriate technique is desirable to characterize the defects of the needle edges. This study aims to develop a characterization technique for measurement of defects such as roughness, chips and tip bending on the edges of needles. The proposed technique uses the diffraction fringes, obtained from the superposition of diffracted light from needle edges and the direct propagated light from the source. Variations in the fringes and their intensity profiles are utilized to study the defects. Further, the results are compared with results obtained from a standard optical profiler and a microscope. The standard deviation of proposed technique for repeatability and reproducibility of measurements are σ = 0. 104 a.u and σ = 0. 87 a.u, respectively. This technique is simple, non-contact in nature, uses compact configuration and is capable for qualitative and quantitative evaluation of the hypodermic needles.